Determination of local potentials in mixed conductors : two examples - Rosenkranz, C.; Janek, Jürgen; Justus Liebig University Giessen (My University, 1995)
Two basic experiments for the measurement of local (electro-)chemical potentials in crystalline mixed conductors, which are exposed to external forces, are reported, (a) The profile of the chemical potential of silver metal in a Wagner-Hebb polarization cell Ag ¦AgBr ¦Pt is measured by means of local potential probes. Deviations from calculated profiles are discussed in terms of either a possible electronic overvoltage at the anodic interface AgBr ¦ Pt or a change of the defect structure of AgBr in the region near the anode, (b) In a second experiment, the ionic overvoltage at an interface AgBr ¦ AgCl is determined, again by means of local potential probes.
Keywords: chemical potential profile; mixed conductors; overvoltage; ddc:540